Optimization of furfural production from hemicellulose of citrullus colocynthis (melon) seed husk using response surface methodology (RSM) - Abba Aji, Umar; Muhammad, Chika; Muhammad Sokoto, Abdullahi; Umar, Shamsu; Lawan Kar, Mustapha; Nurudee Almustapha, Muhammad (International Journal of Advanced Chemistry, 2022)
Global population explosion has led to an increase in demand for chemicals and fuels. Consequently this is accompanied by energy security and environmental challenges such as GHGs emissions. Hence, the need for alternative sources of chemicals from greener sources cannot be overemphasized. Furfural was produced from hemicellulose of citrullus colocynthis (Melon) seed husk (MSH) which involves the simultaneous steps of acid catalyzed hydrolysis/dehydration of the (MSH). A response surface methodology (RSM) was used for furfural production and optimization using MINITAB 17statistical software. Results obtained from RSM for furfural production were analyzed using analysis of variance (ANOVA). A furfural with optimum yield of 75.03% was achieved via degradation of hemicellulose fraction of the MSH at optimized variable conditions of Temperature (220 °C), Acid Concentration (10% H2SO4), and Reaction Time (55 minutes). FT-IR spectrum of the produced furfural showed absorption at 1670cm-1 and 2800cm-1 indicating a conjugated carbonyl functional group and aldehydic hydrogen. The result revealed that the utilization of MSH in furfural production may serve as a viable solution of disposing this agricultural wastes and may address environmental problems associated with fossil fuels when the produced furfural used as a feedstock in industries for biofuels and fine chemicals production.